Collaborative Governance Dalam Program Riset Teknologi Kendaraan Listrik - Ona Martha Nurron; Heru Nurasa; Mas Halimah (Department of Public Administration, Universitas Negeri Surabaya, 2022)
The purpose of this study is to describe the empirical phenomenon of the research consortium of the National Research Program on Electric Vehicle Technology at the Research Organization of Engineering Sciences (OR-IPT), the National Research and Innovation Agency (BRIN) within the framework of governance theory. This study used descriptive qualitative method. Data collection techniques were carried out by interview and study policy documents. Sources of data include the Program Coordinator, document monitoring and evaluation reports on program implementation, minutes of technical meetings, and results of previous research. This study found that collaborative collaboration on the research consortium of the National Research Program on Electric Vehicle Technology at the Research Organization of Engineering Sciences (OR-IPT), the National Research and Innovation Agency (BRIN) can reduce research costs effectively and efficiently, as well as supporting the availability of human resources, expertise and infrastructure.